A bispecific antibody demonstrates limited measurability in routine coagulation assays. Issue 6 (August 2020) - Hartmann, Rudolf; Feenstra, Tjerk; Knappe, Sabine; Schrenk, Gerald; Scheiflinger, Friedrich; Dockal, Michael
Abstract : N/A: Accurate monitoring of coagulation, needed for optimal management of patients with haemophilia A with inhibitors, presents a challenge for treating physicians. Although global haemostatic assays may be used in this population, their utility with nonfactor therapies has yet to be established in the clinical setting. The aim of this study was to assess options for potential haemostatic activity monitoring and feasibility for factor VIII (FVIII)-equivalency measurement with a sequence identical analogue (SIA) to emicizumab using different coagulation assays. SIA was analysed using five commercial chromogenic assays and activated partial thromboplastin time (aPTT) assays including clot waveform analysis using five different triggers. Recombinant FVIII served as a comparator in all assays. Thrombin generation in haemophilia A plasma was measured using extrinsic and intrinsic trigger conditions (tissue factor or Factor XIa). Of the five chromogenic assays, a concentration-dependent increase in Factor Xa was observed with one assay, with human Factor IXa and X reagents. The SIA dose–response signal plateaued at therapeutically relevant concentrations and was nonparallel with FVIII reference, thereby not permitting FVIII-equivalence assessment. aPTT varied between reagents, with aPTT normalization occurring at low and below-therapeutic SIA concentrations. SIA [600 nmol/l (90 μg/ml)] only partially restored thrombin generation in individual haemophilia A patient plasma. FVIII-equivalence of SIA could not be determined using standard FVIII protocols and was found to be highly influenced by assay type, analytical conditions and parameters used for calculation. New and/or modified methodology and standard reagents specific for use with nonfactor therapies are required for their utilization in the clinical setting. Abstract : Supplemental Digital Content is available in the text